Možnosti merania vitality lokálnych spoločenstiev pomocou obydlí - Hanko, Jaroslav (Lidé města, 2024)
This article approaches the concept of the “vitality of local communities” and the possibilities of its measurement. It describes the efforts of researchers to define vitality at the level of regions, cities, or even neighborhoods. With the advent of new technologies, we are experiencing an increase in possibilities and tools to visualize vitality in the form of maps or interactive databases. We are witness to numerous projects that explore the vitality of communities in the USA and Canada, but this approach has penetrated the rest of the world only to a lesser extent and in a significantly altered form. The article notes a selected parameter – the dwellings that people build, adapt, or abandon. Dwellings are a well-researched feature from various anthropological perspectives even historically. Thanks to this, it is possible to quantify the level of vitality of cities through houses. We have much data from field research in a specific location in South-Central Slovakia. With the help of said data, it will be possible to create a locally adapted tool for measuring the vitality of the local community. It can be used as an indicator of the quality of life in terms of local policy-making, urban planning, or development forecasting. Therefore, it can be an important tool in the study of depopulating regions.